Association between self-reported functional capacity measures and postoperative myocardial injury in patients undergoing noncardiac surgeries - Polok, Kamil; Buse, Giovanna Lurati; Mauermann, Eckhard; Ionescu, Daniela; Fronczek, Jakub; Hert, Stefan De; Filipovic, Miodrag; Schimmer, Beatrice Beck; Waes, Judith van; Gillmann, Hans-Jörg; Schultze, Cornelia; Kotfis, Katarzyna; et al. (Kardiologia polska, 2024)
Background: Self-reported functional capacity measures have an uncertain role in the pre-operative cardiovascular risk stratification. Aim: This substudy aimed to evaluate whether self-reported metabolic equivalent (MET) could improve the prediction of postoperative myocardial injury (MI) over other well-established cardiovascular risk factors. Methods: This is a post hoc analysis of an international multicenter prospective cohort study. We recruited patients ≥45 years old who had elective elevated-risk noncardiac surgery in 45 centers across 17 countries between June 2017 and April 2020. The primary outcome was MI defined according to the Fourth Universal Definition of Myocardial Infarction. We measured the proportion of new prognostic information added by self-reported MET using multivariable logistic regression. Results: In total, 860 (41.3%) patients suffered MI. In patients without systematic troponin surveillance, the odds ratio for MI with each 1-point increment in MET equaled 1.03 (95% confidence interval [CI], 0.99-1.07). The new prognostic information, according to the likelihood ratio adequacy index, accounted for 1.5%. Sensitivity analysis, including centers with >90% of patients with routine high-sensitivity troponin T monitoring, showed that MET added 21.8% of new information to the baseline model, and each additional point was associated with a lower risk of MI (odds ratio, 0.86; 95% CI, 0.81-0.91). Conclusions: In elevated-risk noncardiac surgery, self-reported functional capacity measures do not significantly improve the prediction of MI; however, they add new prognostic information in centers with routine perioperative troponin monitoring.
Online veröffentlicht: 14. Mai 2024
Gesehen am 23.04.2025